Anti-Vascular Endothelial Growth Factors as a Potential Risk for Implant Failure: A Clinical Report - Elham Emami; Pierre de Grandmont; Mélanie Menassa; Nicholas Audy; Robert Durand (Case Reports in Medicine)
Knowledge of the risk factors for implant osseointegration is essential for clinical decision-making and optimizing treatment success. This clinical report presents a rare case of implant failure in a patient who received intravitreal injections of a vascular endothelial growth factor (VEGF) inhibitor for the treatment of age-related macular degeneration. Following CARE guidelines, the report presents a case rehabilitated with a mandibular 2-implant overdenture using the immediate-loading protocol and standard procedures. The implants failed within six weeks of immediate loading although primary stability (≥50 Ncm) was achieved during surgery and clinical follow-ups did not show any deviance from standard implant care or patient-related complications. Further investigation suggested that the intake of a VEGF inhibitor may be the cause of failure. This clinical report highlights the importance of systemic risk factors in implant success and their consideration during planning for implant-assisted treatment.